Vittoria agli Assasini! Jak brzmi sukces w grze komputerowej? - Bajew, Mikołaj (Conversatoria Linguistica, 2022)
The paper addresses the issue of the success of the sound of computer game success. To realise this, the author undertook a study of sound samples selected by him, which he considered to be the auditory representation of success in a computer game. The study was carried out with the help of the Reaper computer program and included 9 different sound characters. In the article, the author also reflects on the source and essence of success in a computer game and the game-player-success relationship.